2014
DOI: 10.5093/ejpalc2014a4
|View full text |Cite
|
Sign up to set email alerts
|

The Intimate Partner Violence Responsibility Attribution Scale (IPVRAS)

Abstract: The aim of this study is to present a psychometrically sound instrument to assess intimate partner violence offenders' responsibility attributions: the Intimate Partner Violence Responsibility Attribution Scale. The scale was administrated to 423 adult male intimate partner violence offenders court-mandated to a community-based intervention program. A three factor structure (responsibility attribution to the legal system, responsibility attribution to the victim, and responsibility attribution to the offender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 77 publications
(99 reference statements)
1
41
1
9
Order By: Relevance
“…In fact, research has confirmed that people attribute IPV to the provocative personality of the victims (e.g. Gracia & Tomás, 2014;Lila et al, 2014). The third factor (Abuser Responsible for Violence, ARV), retained items from the IBWB (Saunders et al, 1987) which attributed responsibility directly or indirectly to the victims (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, research has confirmed that people attribute IPV to the provocative personality of the victims (e.g. Gracia & Tomás, 2014;Lila et al, 2014). The third factor (Abuser Responsible for Violence, ARV), retained items from the IBWB (Saunders et al, 1987) which attributed responsibility directly or indirectly to the victims (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reliable instruments for which psychometric are available, these include the Inventory of Beliefs about Wife Beating (IBWB, Saunders, Lynch, Grayson, & Linz, 1987), the Domestic Violence Myth Acceptance Scale (Peters, 2008) and the Intimate Partner Violence Responsibility Attribution Scale (IPVRAS, Lila, Oliver, Catalá-Miñana, Galiana, & Gracia, 2014). Of the instruments mentioned, the IBWB is the only one designed to assess general and specific attitudes towards domestic violence; the DVMAS assesses perceptions of myths about domestic violence (Peters, 2008) and the IPVRAS assesses perpetrators' attributions of responsibility for IPV.…”
Section: Measuring Attitudes To Ipvmentioning
confidence: 99%
“…Benevolent sexism, on the other hand, is based on men's need for and reliance on women (e.g., "No matter how accomplished he is, a man is not truly complete as a person unless he has the love of a woman"). This inventory has been validated and adapted to more than twenty countries (Glick et al, 2000;Glick, Sakall, Urgurlu, Ferreira, & Aguilar de Souza, 2002), and has proved to be strongly related to IPVAW responsibility attribution and to attitudes toward intervention in IPVAW cases among police officers Lila, Oliver, Catalá-Miñana, Galiana, & Gracia, 2014). Both subscales showed a good internal consistency in the sample of this study (Cronbach's α = .88 and .89 for hostile and benevolent sexism, respectively).…”
Section: Instrumentsmentioning
confidence: 99%
“…O que, desde então, com a crescente participação criminal do fenómeno, se tem vindo, a verificar uma multiplicidade de pedidos de ajuda aos sistemas formal e judicial (Duarte, 2013;Machado et al, 2009). A par desta ação, a partir da década de 90, em Portugal, verifica-se também, um número crescente de trabalhos de investigação sobre tal tipo de violência, sobre a sua prevalência e dimensão (Machado et al, 2014) e uma compreensão mais qualitativa do fenómeno (Lila, Germes,Miñana, Llinares, & Gracia, 2014;Machado & Matos, 2001;Matos, 2000); constituindo-se, assim, um reflexo de uma maior sensibilidade face ao fenó-meno violência conjugal (Fatela, 1989;Winstok, 2016;Winstok, & Sowan-Basheer, 2015) e intolerância social face a comportamentos violentos. Do mesmo modo, é um fenómeno que vem sendo objeto de particular atenção de políticos, juristas, sociólogos, psicólogos e toda a espécie de curiosos, sobretudo, ligados a grupos de pressão com intervenção social; tratando-se de um complexo problema social, que o devir comunitário e a crescente consciência coletiva sobre a dimensão e efetividade dos direitos, vem impondo (Colossi, 2015;Alves et al 2012;Dias, 2004;Pinheiro et al 2012;Santos e Costa, 2004).…”
Section: Introductionunclassified